2022
DOI: 10.3390/ijerph20010410
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Experiences Using Digital Health Technologies in Paediatric Overweight and Obesity Support: An Integrative Review

Abstract: This study aimed to explore parents’ perspectives regarding the use of digital health technologies in paediatric overweight and obesity weight support. A systematic search in ‘Academic Search Premier’, ‘British Nursing Index’, ‘Cumulative Index to Nursing and Allied Health’, and ‘Health Research Premium Collection’ was conducted in November 2021. Inclusion criteria were English or Nordic peer-reviewed articles published after 2010, overweight and obese children aged 2–10, weight support using digital health te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Family environments play a pivotal role in the context of obesity: it must be protective and anti-obesogenic, especially due to the strong influence of parent's habits on their children's habits. Goa et al (89) analyzed 14 articles that evaluated parent's experiences and needs in the use of mHealth strategies, such as SMS, telephone, apps, websites, and social media, in the management of overweight or obese children aged 2-10. They demonstrated that technologies are considered a useful tool by parents, but it is important to involve them in the development of mHealth strategies, in order to design suitable tools to meet the family needs.…”
Section: Discussionmentioning
confidence: 99%
“…Family environments play a pivotal role in the context of obesity: it must be protective and anti-obesogenic, especially due to the strong influence of parent's habits on their children's habits. Goa et al (89) analyzed 14 articles that evaluated parent's experiences and needs in the use of mHealth strategies, such as SMS, telephone, apps, websites, and social media, in the management of overweight or obese children aged 2-10. They demonstrated that technologies are considered a useful tool by parents, but it is important to involve them in the development of mHealth strategies, in order to design suitable tools to meet the family needs.…”
Section: Discussionmentioning
confidence: 99%
“…Telehealth has an additional important benefit to those listed above, which is high parent and patient satisfaction. One review of various telehealth methods (SMS, email, social media, video calls, phone calls, web-based systems, or apps) found that most parents had an overall positive experience with using digital health technology in pediatric overweight and obesity [24], reporting that they saved time and money on travel and found it to be generally convenient. A survey of caretaker opinions regarding telehealth conducted during the COVID-19 pandemic listed quality communication with physicians, savings in travel time, and cost-effectiveness, yet identified challenges such as lack of in-person interaction (as we also certainly felt in the clinic), fear of compromised confidentiality, and the potential for misdiagnosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of such digital devices can compromise sleep, attention, and learning; increase the incidence of obesity and depression; and expose people to inaccurate, insensitive, or unsafe information [21]. In contrast, a recent study suggests that digital devices can empower parents who are concerned about their children's overweight and obesity [22]. Studies have found an increased incidence of high BMI in children and adolescents who use digital devices [23][24][25][26][27], including ordering food online.…”
Section: Literature Reviewmentioning
confidence: 99%